2010
DOI: 10.5012/bkcs.2010.31.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Modeling, Virtual Screening and Molecular Docking Studies for Identification of New Inverse Agonists of Human Histamine H1Receptor

Abstract: Human histamine H1 receptor (HHR1) is a G protein-coupled receptor and a primary target for antiallergic therapy. Here, the ligand-based three-dimensional pharmacophore models were built from a set of known HHR1 inverse agonists using HypoGen module of CATALYST software. All ten generated pharmacophore models consist of five essential features: hydrogen bond acceptor, ring aromatic, positive ionizable and two hydrophobic functions. Best model had a correlation coefficient of 0.854 for training set compounds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(14 reference statements)
2
12
0
Order By: Relevance
“…Previous studies have also reported similar pharmacophore models for HHR1 antagonists [53]. As reported earlier, the distance between the PI function (generally the basic nitrogen atom) and the aromatic part of the ligand ought to be around 6 Å [32,54]. In our model, it is 6.267 Å between PI and RA, and 6.361 Å between PI and HP features, respectively.…”
Section: Pharmacophore Modellingsupporting
confidence: 50%
See 2 more Smart Citations
“…Previous studies have also reported similar pharmacophore models for HHR1 antagonists [53]. As reported earlier, the distance between the PI function (generally the basic nitrogen atom) and the aromatic part of the ligand ought to be around 6 Å [32,54]. In our model, it is 6.267 Å between PI and RA, and 6.361 Å between PI and HP features, respectively.…”
Section: Pharmacophore Modellingsupporting
confidence: 50%
“…BLAST (blastp) search [43] as implemented in DS against Protein Data Bank (PDB) was employed to search for the proteins that are crystallographically determined and closely related to HHR1. As an update to our previous study, where squid rhodopsin was used as a template to build homology models [32], recently determined GPCR proteins, namely adenosine A2A receptor (A2AR) [44] and b2 adrenergic receptor (B2AR) [45] of human were used as possible templates from the BLAST search to build two different homology models of HHR1. The Align Multiple Sequences protocol of DS was utilised to align the template and the target sequences.…”
Section: Homology Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…This further necessitates exploration of the binding preferences of the known inhibitors in the context of structure activity relationship and the identification of potential novel lead molecules against PTR1. Pharmacophore modeling is one of the best 3D-QSAR methods which have been successfully applied to drug discovery process [19,20]. In the present study, based on the knowledge of the L. major inhibitors of PTR1 in the literature and the co-crystal structures of the complexes of the same; pharmacophore modeling, docking, and 3D QSAR studies have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported with Olopatadine-related compounds, that is, dibenzoxepin-7-carboxylic acid compounds showed weaker H 1 binding affinity than dibenzooxepin-3-carboxylic acid compounds. 20 Thangapandian et al have reported that the lipophilic cavity in H 1 receptor take part in antagonist binding, 21 and Ram et al have reported that phenyl or indole rings interact with electron rich group in H 1 receptor. 22 Therefore, it is believed that the position of the oxygen atom in dibenzooxazepins can affect lipophilic interaction.…”
Section: Resultsmentioning
confidence: 98%